Synthesis and Biological Evaluation of tert‐Butyl‐5‐methylpyrimidin‐piperazine Derivatives as Anti‐Obesity Agents. Issue 12 (15th September 2014) - Chen, Jinying; Pu, Yuzhi; Pei, Heying; He, Linhong; Fu, Suhong; Chen, Lijuan
<x xml:space="preserve">Abstract</x> A series of tert‐butyl‐5‐methylpyrimidin‐piperazine derivatives were synthesized and their anti‐obesity activities were evaluated. Compounds 4g and 5j were found to have significant effects in down‐regulating the triglyceride level of 3T3‐L1 adipocytes. 5j exhibited remarkable therapeutic effects on the diet‐induced obesity (DIO) mouse model at 20 mg kg−1 day−1 for 4 weeks by decreasing the weights of body, liver, and fat. 5j also regulated serum biomarkers to appropriate ranges, exerted therapeutic activity of steatosis in liver tissue and ameliorated the obese‐related symptoms. In addition, 5j significantly decreased the blood glucose levels in oral glucose tolerance tests and improved the insulin sensitivity in insulin tolerance tests. These results suggest that 5j could be a candidate for obesity treatment.